Contribution of objective and subjective attributes to the variation in the whiteness and brightness of commercial mohair sale lots. Issue 4 (2nd April 2016) - McGregor, B.A.; Stapleton, D.L.
Abstract : Colour properties are measured prior to the sale of merino wool as they are of commercial importance when greasy wool is sold and when wool is dyed. With the paucity of knowledge of the colour properties of commercial mohair, this study aimed to identify and quantify the factors affecting the brightness ( Y ) and yellowness ( Y - Z ) values of commercial lots of Australian mohair. The research database comprised 520 sale lots (>500, 000 kg mohair), which had tristimulus tests, and was sold during the period 2001–2009. Mohair was subjectively classed and sale lots objectively tested using international standard methods for mean fibre diameter (MFD, μm), fibre diameter coefficient of variation (%), International Wool Testing Organization (IWTO) clean wool base (IWTO yield, %w/w), vegetable matter (VM, %w/w) and the tristimulus values X, Y and Z ( T units). The tristimulus values of Australian mohair were affected by the objective measurements of MFD, VM%, the subjective classing of stain, cotting, kemp and length and by the year and selling season. Variation in Y was more easily predicted with 90.5% of variance explained by the best model compared with variation in Y - Z, where the best model explained 51.6% of the total variance. Visually assessed properties of the mohair were very important in separating mohair of different Y properties, accounting for almost 80% of the total variance, but were far less important in accounting for the variance in Y - Z, accounting for about 9–10% of the total variance. The most important effects on the Y of mohair were associated with subjectively determined fault categories determined before the sale of mohair. In particular, stain fault explained about two-thirds of the variance in brightness of mohair sale lots. Stained mohair had much lower brightness than mohair free of stain but stain fault explained very little of the variation in yellowness of mohair sale lots. The extent of the differences in tristimulus values between seasons and years were not large for Y but were more important for yellowness ( Y - Z ), and these effects are likely to be of commercial importance. Generally, brightness decreased and yellowness increased as MFD increased up to about 30 μm. Both cotting and kemp fault were associated with reduced brightness and increased yellowness. The effects of VM% on tristimulus values were small. IWTO yield was associated with changes in tristimulus values, but in the best model, IWTO yield was not a significant determinant. This study indicates that commercial Australian fleece (nonfaulted) mohair was essentially white. Faulted mohair on the other hand exhibited poorer colour characteristics. The mohair subjectively identified as stained prior to sale comprised all the mohair which would be regarded as not white, and this investigation indicates that the effect of staining is on the brightness of mohair rather than the Y - Z measurement. Unlike the situation with merino wool, there was little relationship between the naturally occurring contaminants, as measured by the IWTO washing yield, and either Y or Y - Z .